Fetal head size and effect of manual perineal protection - Jansova, Magdalena; Kalis, Vladimir; Rusavy, Zdenek; Räisänen, Sari; Lobovsky, Libor; Laine, Katariina (PloS one, 2017)
OBJECTIVE: The aim of this study was to evaluate whether a previously identified modification of Viennese method of perineal protection remains most effective for reduction of perineal tension in cases with substantially smaller or larger fetal heads. METHODS: A previously designed finite element model was used to compare perineal tension of different modifications of the Viennese method of perineal protection to "hands-off" technique for three different sizes of the fetal head. Quantity and extent of tension throughout the perineal body during vaginal delivery at the time when the suboccipito-bregmatic circumference passes between the fourchette and the lower margin of the pubis was determined. RESULTS: The order of effectiveness of different modifications of manual perineal protection was similar for all three sizes of fetal head. The reduction of perineal tension was most significant in delivery simulations with larger heads. The final position of fingers 2cm anteriorly from the fourchette (y = +2) consistently remains most effective in reducing the tension. The extent of finger movement along the anterior-posterior (y-axis) contributes to the effectiveness of manual perineal protection. CONCLUSION: Appropriately performed Viennese manual perineal protection seems to reduce the perineal tension regardless of the fetal head size, and thus the method seems to be applicable to reduce risk of perineal trauma for all parturients.
Keywords: Obstetric Labor Complications; plod; Finite Element Analysis; analýza metodou konečných prvků; Humans; hlava; lidé; Female; Fetus; Pregnancy; Head; těhotenství; komplikace porodu; Delivery, Obstetric; Perineum; vedení porodu; ženské pohlaví; perineum